ANALISIS KEUANGAN DAERAH KABUPATEN KUBU RAYA DALAM RANGKA PELAKSANAAN OTONOMI DAERAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - B61110028, ZULKARNAIN (Jurnal Ekonomi Daerah (JEDA), 2014)
ABTRACT This Research gets title â€œFinancially Region Analized in Kubu Raya Regency in Order to Autonomous Performing and the Factor of Regarding It,â€ by `Zulkarnain`, is one of case study research that is done at Kubu Raya Regency. To the effect of this research is to analized of increaseed region finance independence, PAD (the original regional revenue)'S effectiveness, growth and Elasticity to PDRB and population, and to analized of constraint and interference in PAD'S management at Kubu Raya Regency. This is descriptive observational analisis, data that utilized by stem from BPS (Kubu RayaRegency in Figure) derivative 2010 until 2012. Supporting datas (primary data) of on duty financial Management Income and Region wealth (DPPKAD) Kubu Raya Regency as write-up as regions accepting realization in APBD, and observing result data and interview. Result observationaling to point out that Regency financial independence zoom Kubu Raya Regency really low each year under 10 %, with average 4,37%, dependable level matter on federal as big as 95,63%. Elasticities arithmetic result PAD to PDRB average 4,14 (elastic). Meanwhile PAD'S elasticity to population/resident average 12,31 (elastic). Itâ€™s mean is added islandic so far-reaching to PAD'S step-up, 1 equal 12,31, its mean is islandic one percent (1%) ascension cause PAD'S ascension 12,31%. PAD'S accepting effectiveness tends to experience decrease each year, year 2011 constitute supreme contribution tops, this constitute consequence of UU No. 28/2009 applied. But on 2012 happenings too low contribution of PAD,Â  since its dwindling BPHTB'S taxes contribution arising out marks sense moratorium uncovering limit and also horticultural permit prolongation year oil palm 2012. Faced constraint in picking PAD is is still a lot of taxes which was or not be charged especially on year 2012, also consequent of another technical constraint amongst those its reducing person, and its reducing assessable consciousness in pay taxes/retribution and identification that wasâ€™n optimal. Â  Keyword: Â Â Â  Regionals Original Revenue, Effectiveness, Elasticity, Degree Fiscal Decentralisation.